ODEF: an interactive tool for optimized design of EMI filters - Di Piazza, M.C.; Luna, M.; Vitale, G.; Ala, G.; Giaconia, G.C.; Giglia, G (2016)
The impact of EMI filters on volume and weight of power converters is significant. For this reason, filter’s size optimization is a strategic step towards the improvement of the power converter’s power density. An EMI filter design that follows a conventional procedure does not guarantee the selection of components/configuration leading to the best power density. Therefore, in order to help EMI engineers and scientists in pursuing a fast and effective choice of optimal discrete EMI filter components and configuration, a novel tool is proposed in this paper, namely ODEF (Optimized Design of EMI Filters). ODEF is an interactive software application running in Matlab® environment. It suitably improves a previously validated EMI filter design procedure that extends the conventional filter design method in order to achieve optimal power density. Features and operation of ODEF tool are illustrated. Moreover, the experimental assessment of an input EMI filter, designed according to the optimized procedure for an inverter-fed induction motor drive, is performed.